Wear Behavior of a Heat-Treatable Al-3.5Cu-1.5Mg-1Si Alloy Manufactured by Selective Laser Melting - Pei Wang (MDPI AG, 2021)
In this study, the wear behavior of a heat-treatable Al-7Si-0.5Mg-0.5Cu alloy fabricated by selective laser melting was investigated systematically. Compared with the commercial homogenized AA2024 alloy, the fine secondary phase of the SLM Al-Cu-Mg-Si alloy leads to a low specific wear rate (1.8 ± 0.11 × 10−4 mm3(Nm)−1) and a low average coefficient of friction (0.40 ± 0.01). After the T6 heat treatment, the SLM Al-Cu-Mg-Si alloy exhibits a lower specific wear rate (1.48 ± 0.02 × 10−4 mm3(Nm)−1), but a similar average coefficient of friction (0.34 ± 0.01) as the heat-treated AA2024 alloy. Altogether, the SLM Al-3.5Cu-1.5Mg-1Si alloy is suitable for the achievement of not only superior mechanical performance, but also improved tribological properties.